Manajemen Pengembangan Kompetensi Tenaga Pendidik Di Madrasah - Beny Sintasari (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2024)
This research aims to analyze the management of competency development for teaching staff at MA Darul Ulum Bandung Jombang. The method used is qualitative with data collection techniques through observation, interviews and documentation. The research results show that the professionalism competency of teaching staff at MA Darul Ulum Bandung Jombang has reached a good level. This competency development occurs through an effective planning, implementation and evaluation process. Planning is carried out through regular supervision and work meetings to identify teacher training needs. Implementation is carried out through training and workshops which teaching staff must attend every year. Evaluation is carried out after training or workshops to evaluate the achievements and success of teaching staff. Thus, it can be concluded that MA Darul Ulum Bandung Jombang has succeeded in managing and increasing the professional competence of its teaching staff, which is an important basis for improving the quality of education at the institution.